Tinjauan Kelengkapan Pengisian Lembar Informed Consent Pasien Rawat Inap di RSU Adhyaksa - Feni Fajriani; Deasy Rosmala Dewi; Nanda Aula Rumana; Muniroh (Yayasan Literasi Sains Indonesia, 2022)
Informed Consent is an agreement given by the patient or his closest family after receiving a complete explanation regarding the medical or dental action to be performed on the patient. Minimum Service Standards for Hospitals which mention filling out Informed Consent must be 100% complete after receiving clear information. This study was conducted with the aim of obtaining the completeness of filling out the consent form for medical treatment for inpatients at Adhyaksa General Hospital. This study uses a quantitative approach with a descriptive method. Based on the research results, the process of filling out the Informed Consent sheet at Adhyaksa RSU is not complete, from the research results of the Information Provider section on the Declaring Identity component by 75%, Completeness of Important Reports by 64%, Author Authentication by 85%, Good Records by 77%. The Informed Consent section on the Identity component is 95%, the Completeness of Important Reports is 91%, Author Authentication is 93%, Good Records is 84%. Adhyaksa General Hospital does not yet have an SOP. Fill out the informed consent form. The existing SOP on Informed Consent. The author's suggestion is that the hospital must re-socialize it to medical personnel so that the filling out of the medical action approval sheet is more complete according to minimum service standards.